Nakagami, Japan : Buraku and the Writing of Ethnicity - McKnight, Anne, 1966- (Book collections on Project MUSE., 2011)
How do you write yourself into a literature that doesn't know you exist? This was the conundrum confronted by Nakagami Kenji (1946û1992), who counted himself among the buraku-min, Japan's largest minority. His answer brought the histories and rhetorical traditions of buraku writing into the high culture of Japanese literature for the first time and helped establish him as the most canonical writer born in postwar Japan. In Nakagami, Japan, Anne McKnight shows how the writer's exploration of buraku led to a unique blend of fiction and ethnographyùwhich amounted to nothing less than a reimagining.